Technology readiness and purchase intention: role of perceived value and online satisfaction in the context of luxury hotels. (16th December 2019) - Pham, Long; Williamson, Stan; Lane, Peggy; Limbu, Yam; Nguyen, Pham Thi Hoan; Coomer, Tatyana
This study investigates the relationships among customer technology readiness, perceived value, satisfaction with hotel website integrated self-service technologies, and purchase intention. The data for this study were collected from 668 international tourists who stayed in major cities' luxury hotels in Vietnam. Data were analysed using structural equation modelling technique. The results indicated that optimism and innovativeness positively influence customer perceived value, and insecurity negatively influences customer perceived value; optimism and innovativeness positively influence customer satisfaction; insecurity negatively influences customer purchase intention; customer perceived value positively influences customer satisfaction and customer purchase intention; and customer satisfaction positively influences customer purchase intention. Theoretical contributions and managerial implications are discussed.